Pemanfaatan Artificial Intelligence untuk Meningkatkan Literasi Numerasi Siswa di SMP Insan Rabbany - Noni Dwi Sari; Putri Gusmarini; Marlina Marlina; Nurjana Nuraita; Luthfiani Hardyanti Moinori; Lia Nurlaila (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Numeracy is an essential competency that supports students’ ability to reason quantitatively and solve real-life problems. However, students in Indonesia often face challenges in understanding mathematical concepts and applying them in everyday contexts. In response to this, a community service program was conducted at SMP Insan Rabbany, Tangerang Selatan, focusing on the integration of Artificial Intelligence (AI) applications such as ChatGPT and Educaplay in mathematics learning. The program aimed to improve students’ numeracy literacy and provide teachers with the capacity to utilize AI tools effectively. The activities included training sessions for teachers, and direct assistance in classroom implementation. The results showed a significant uses in students’ ability of numeracy. Moreover, teachers expressed increased confidence in incorporating AI-based methods into their lessons. This program highlights the potential of AI to enhance numeracy skills and underscores the importance of technological support and teacher training in the digital age.